The protection of the Islamic minority beyond religious freedom: legal pluralism and reasonable accommodation in Europe (Stato, Chiese e pluralismo confessionale, 2024)
ABSTRACT: In Europe's diverse societal landscape, the Islamic minority, or a significant portion thereof, seeks to navigate life under Sharia law, especially concerning family matters. Despite the fact that the application of Sharia law, where permitted, has demonstrated its ability to adapt to the legal context, as in the case of Islamic arbitration, in the case of family law, the perception of an irreducible contrast with the values of Western countries appears particularly strong producing an inevitable paradox in relation with freedom of religion that may be restricted by the legal system. The core paradox lies in the potential infringement on religious freedom if Muslims were asked to forsake religious tenets or practices that align with the foundational principles of the legal system. Modern legal frameworks are thus challenged to find methods to harmonize the identity assertions of Islamic communities with the safeguarding of individual rights within these communities. With no specific safeguards for religious minorities, this study scrutinizes jurisprudence on family law from selected European courts. The objective is to unearth effective legal tools that respect the Islamic community's minority religious identity while upholding the essential tenets of the legal system, fostering a balance between collective religious identity and individual rights protection in a multicultural Europe.SUMMARY: 1 - Religious minorities between cultural identity and religious freedom: preliminary remarks - 2. Legal Pluralism and Religious Pluralism: Protection tools for religious minorities - 3. Muslims of Europe - 4.- The Interaction Between Sharia and the Legal System of the State: Techniques of Reasonable Accommodation and Islamic Family Law - 5. The protection of the Islamic minority beyond religious freedom: concluding remarks.